(untitled) (Indian Journal of Arid Horticulture, 2025)
Date palm (Phoenix dactylifera L.) is a nutritious fruit and provides high calories of energy. It is rich source of carbohydrates, minerals, vitamin A, B, and B, Date palm is mostly suitable for cultivation in arid regions of the country where irrigation facilities are available. It is drought hardy plant and tolerates salinity and aridity. It requires rainless period during fruiting season particularly at the time of ripening. In order to exploit the potential of the north-western dry regions of India for date palm cultivation, a number of varieties have been introduced from Middle East countries, USA, which is performing better in different parts of country (Chandra et. al. 1990). Introduction of new varieties having better traits is a continuous process to enrich genetic resource and productivity of crops. In India, date palm is mainly cultivated in western parts of Rajasthan, Kachchh region of Gujarat, Punjab and Haryana. The districts of Rajasthan such as Jaisalmer, Barmer, Bikaner, Jodhour are extremely dry and suitable for date palm cultivation. In addition to this, parts of Sri Ganganagar, Churu, Nagour, Hanumangarh, Sirsa, Sikar are also suitable for date production (Mertia and Vashishtha, 1985). In Kachchh region of Gujarat, date palm is growing in about 12,493 ha area with production of 85.352 tonne doka stage fruits .